Biodegradation of Pharmaceuticals by Fungi and Metabolites Identification - Cruz Morató, Carles (2012)
Pharmaceutical compounds comprise a widely employed group of therapeutic agents now considered as emerging micropollutants. This chapter summarizes the state of the art in the degradation of pharmaceuticals by fungi in liquid matrices (with emphasis on white-rot fungi), including the use of both whole cells and fungal enzymes. The identification of the metabolites produced as well as the proposed degradation pathways available for some drugs are discussed. The information is organized according to the activity of the pharmaceutical compounds, grouped in: anti-inflammatory/analgesic drugs, psychiatric drugs, lipid regulators, antibiotics and other antimicrobial agents, b-blockers, estrogens, and iodinated contrast media. Considering the interest in potential application of fungal treatments in future real scale bioremediation of effluents, the ecotoxicology of the process is included when available.